STUDY ON HEAVY METALS CONCENTRATION IN IRRIGATED SOIL SAMPLES OF SOME SELECTED LOCATIONS ALONG RIVER KADUNA, NIGERIA - T. Y, Liatu; I.K, Auta; Kurdan, Tanko; E.N, Gajere; Magu, Joshua (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
The use of dumpsites for irrigation farming is a common practice in urban and sub-urban areas inNigeria because of the fact that decayed and composted wastes enhance soil fertility. Thesewastes often contain heavy metals in various forms and at different contamination levels. Thisstudy was conducted to ascertain the level of contamination of heavy metals in irrigation soil.Thirty composite soil samples (0-30cm depth) representing irrigation soils in Karji, Gamji resort,Stadium-under the bridge, Tudunwada and Kudandan were sampled during November to April2015/2016 (pick irrigation period) and heavy metals such as Chromium (Cr), Cadmium (Cd),Lead (Pb), Mercury (Hg) and zinc (Zn) were determined using Atomic AbsorptionSpectrophotometer, after digestion by nitric acid procedure. The heavy metal concentration in thesoil ranged from: Cadmium, 17.89±3.13 to 31.75±1.27; Chromium, 37.32±12.32 to 88.14±4.34;Mercury, 0.01±0.00 to 0.32±0.50; Lead, 46.00±12.18 to 99.45±33.67 and Zinc, 26.34± 6.48 to98.53±24.98 mg/kg. The concentrations of Cadmium and Lead were above standard limit set byE.U and DPR therefore advocating a health risk to the consumers of produce from theselocations since plants absorbs heavy metals from soils through the root. The significantvariations observe in concentration of heavy metals from one location of study to another wastraced to different levels of pollution, caused by different degree of industrial and domestic wastedumps and other waste deposits on the soil